Post-silking Phosphorus Recycling and Carbon Partitioning in Maize Under Low to High Phosphorus Inputs and Their Effects on Grain Yield - Wang, Chao; Ning, Peng (Frontiers in Plant Science, 2019)
Phosphorus (P) recycling and carbon partitioning are crucial determinants of P-use efficiency and grain yield in maize (Zea mays), while a full understanding of how differences in P availability/plant P status affect these two processes underlying yield formation remains elusive. Three-year field experiments were conducted to investigate the maize growth, P remobilization, and carbohydrate accumulation in leaves and developing ears in plants receiving low to high P inputs. The results showed that the increases of leaf area, ear growth and grain yield stagnated when soil Olsen-P concentration beyond about 7.5 mg kg-1, while P uptake increased as P fertilization even over this threshold, resulting in a lower P-use efficiency. Regardless of P supply, P remobilization preferentially occurs from stem (50-76%) than from leaves (30-44%), and has priority from inorganic P (Pi) over organic P fractions during the first half of grain filling phase. Leaf photosynthesis was maintained under P-limiting conditions due to the greater P investment to the organic pools than Pi, and more and larger starch granules were found in the bundle sheath cells at silking or 21 days after silking (DAS) than under P-sufficient conditions. Taken the smaller leaf size and lifespan into consideration, the total production of carbohydrates and export for growth were less in the P-deficient plants than in the high P plants. Nonetheless, similar or significantly greater starch levels were observed in both cob and kernels at silking and 21 DAS, implying carbohydrate transported to developing ears seemed relatively enough for the diminished kernel sink under P starvation. In addition, strong correlation was observed between the accumulation rates of carbon and remobilized P in the developing kernels, as well as between carbon and total P. Overall, an integrated framework considering post-silking P recycling and carbon partitioning in maize and their effects on grain yield were proposed. It was likely due to the severely diminished sink size to constrain carbon deposition in P-deficient plants, which in turn imposes a feedback regulation reducing carbon and P mobilization from source leaves.